The Role of Geographical Factors in The Socio-Economic Development of Surkhandarya Region (Texas Journal of Multidisciplinary Studies, 2021)
This article discusses the geographical location, climate and factors that make up Surkhandarya, the southernmost region of the Republic of Uzbekistan. recommendations are illuminated